The legal concept of emerging crimes and its relation to Organized Crime - أوتاني, صفاء; نصر, مهيب (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The growth of crime rate became a serious concern for all the international community as emerging crimes started to appear in all human transactions and behaviors. Emerging crime became an inseparable part of the overall social system of the international community especially in the light of globalization changes, industrial renaissance in addition to the technological and informatics revolution. This was a result of opening of the countries on the outside world in addition to the social interaction between different peoples. The "industrial revolution" in Europe, which was followed by a "social and secular revolution", is considered as a starting point for globalization. This is because it changed the social, legal and philosophical infrastructure of countries and societies as a whole. Since the 1990s, the "knowledge and information economy" sector has been formed. This sector led to a new civilized leap in history, which had a great role in developing and modifying the forms and patterns of the criminal phenomenon according to the new global system. Novelty of the behaviors, methods and forms of the criminal phenomenon required studying its concepts and causes in addition to the extent of its relation to the rapid changes we are experiencing through high-tech means of communication. Thus, it is crucial to spot light on the emerging criminal phenomenon and the impact of globalization tools on it through reviewing its concepts and some of its features and forms.